2006
DOI: 10.1111/j.1752-0606.2006.tb01587.x
|View full text |Cite
|
Sign up to set email alerts
|

MARRIAGE AND FAMILY THERAPIST INTERNs' EXPERIENCES OF GROWTH

Abstract: In this study, I explored marriage and family therapist interns' growth experiences, both personal and professional, and the interplay between them. Participants discussed, using Internet discussion board and chat room formats, different kinds of personal experiences that influenced their clinical growth (as well as the reverse) and how these growth processes came about. Family systems theory provided the theoretical framework and Constructivism theory guided the manner in which the study was conducted. Thirte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 36 publications
(76 reference statements)
2
14
0
Order By: Relevance
“…The findings in this study are consistent to some degree with results from the prior studies conducted by Nel (2006) and Paris et al (2006). Nel found that trainees reflected on personal relationships, both in the present and the family of origin, but more emphasis was placed on the stresses of training and it's effects on family life as well as the tension involved in balancing work, training, and motherhood.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The findings in this study are consistent to some degree with results from the prior studies conducted by Nel (2006) and Paris et al (2006). Nel found that trainees reflected on personal relationships, both in the present and the family of origin, but more emphasis was placed on the stresses of training and it's effects on family life as well as the tension involved in balancing work, training, and motherhood.…”
Section: Discussionsupporting
confidence: 92%
“…It is also interesting that the majority of the aspects of training listed as responsible for personal development involved trainees actually doing relationships rather than learning family therapy skills. The findings of this study and the two prior studies by Nel (2006) and Paris et al (2006) exemplify a culture of teaching in family therapy that aims to foster relational expertise, not simply the development of technical proficiency in interviewing and intervention.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…How did this experience color her perspective and challenge her internal rubrics of what marriage and coupling actually means? For both clinicians, who were at the training stage, what opportunities did they have to discuss the critical intersections of who they were personally and who they were professionally (Paris, Linville, & Rosen, 2006)? In addition, when considering the self-of-the-therapist issues, how might this have intersected with their feelings of inadequacy or lack of readiness in serving this transgender-lesbian couple (Long & Bonomo, 2006)?…”
Section: Where To Go From Herementioning
confidence: 99%
“…Yet the underlying benefit to their clients was the safety these student counselors provided in the room for this couple, which ultimately has much more to do with who they are personally. More time on this could have enhanced the quality of their clinical work and potentially allowed for even more risk taking to assist this unique couple's navigation of their crucial dilemma of sexual incompatibility (Paris et al, 2006).…”
Section: Where To Go From Herementioning
confidence: 99%